Retracted: MiR‐485‐3p serves as a biomarker and therapeutic target of Alzheimer's disease via regulating neuronal cell viability and neuroinflammation by targeting AKT3. Issue 1 (21st November 2020) - Yu, Ling; Li, Haiting; Liu, Wenhu; Zhang, Ligong; Tian, Qun; Li, Hairong; Li, Min
Abstract: Background: Numerous microRNAs (miRNAs) have been identified as functional molecules in Alzheimer's disease (AD) pathogenesis. This study aimed to investigate the diagnostic value of microRNA‐485‐3p (miR‐485‐3p) in AD patients, evaluate the effect of miR‐485‐3p on neuronal viability and neuroinflammation, as well as the underlying molecular mechanisms. Methods: Quantitative Real‐Time PCR was used to estimate expression of miR‐485‐3p and AKT3. A ROC analysis was used to evaluate the diagnostic value of miR‐485‐3p. The correlation of miR‐485‐3p with patients' MMSE score and inflammatory response was analyzed. Using Aβ‐treated SH‐SY5Y and BV2 cells models, the effects of miR‐485‐3p on neuronal proliferation, apoptosis, and neuroinflammation were explored. A luciferase reporter assay was used to confirm the target gene of miR‐485‐3p in both SH‐SY5Y and BV2 cells. Results: Serum miR‐485‐3p expression was significantly upregulated in AD patients and cell models, which had a high diagnostic accuracy and correlated with MMSE score and inflammatory response in AD patients. The knockdown of miR‐485‐3p in SH‐SY5Y and BV2 cells was found to significantly reverse the effect of Aβ treatment on neuronal viability and neuroinflammation. AKT3 was determined as a target of miR‐485‐3p, which might mediate the biological function of miR‐485‐3p in AD pathogenesis. Conclusion: All the data indicated that increased serum miR‐485‐3p serves as a diagnostic biomarker in AD patients, and knockdown of miR‐485‐3p exerts a neuroprotective role by improving neuronal viability and weakening neuroinflammation, which may be mediated by AKT3. This study may provide a novel biomarker and therapeutic target for AD therapy. Abstract : This study aimed to investigate the diagnostic value of microRNA‐485‐3p (miR‐485‐3p) in AD patients, evaluate the effect of miR‐485‐3p on neuronal viability and neuroinflammation, as well as the underlying molecular mechanisms. All the data indicated that increased serum miR‐485‐3p serves as a diagnostic biomarker in AD patients, and the knockdown of miR‐485‐3p exerts a neuroprotective role by improving neuronal viability and weakening neuroinflammation by targeting AKT3. This study may provide a novel biomarker and therapeutic target for AD therapy.